2013
DOI: 10.1159/000350752
|View full text |Cite
|
Sign up to set email alerts
|

Is Urinary Soluble Fas an Independent Predictor of Non-Muscle-Invasive Bladder Cancer? A Prospective Chart Study

Abstract: Objectives: To evaluate whether soluble Fas (sFas) in urine is an independent predictor of non-muscle-invasive bladder cancer (NMIBC). Methods: We performed a prospective chart review which included 128 subjects with NMIBC and 88 controls. The first morning voided urine sample (10-20 ml) was obtained from preoperative patients and controls. Expression levels of sFas in urine were analyzed using enzyme-linked immunosorbent assay. Clinical and pathological data, European Organisation for Research and Treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In recent years, the research based on Fas/FasL system has become one of the important advances in the field of molecular biology [ 11 , 12 ], and higher sFas levels in the serum have been investigated in various cancer types [ 4 , 13 , 14 ]. Mizutani et al [ 15 ] reported elevated sFas levels in the serum of patients with bladder cancer and suggested an association of elevated sFas level with poor prognosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the research based on Fas/FasL system has become one of the important advances in the field of molecular biology [ 11 , 12 ], and higher sFas levels in the serum have been investigated in various cancer types [ 4 , 13 , 14 ]. Mizutani et al [ 15 ] reported elevated sFas levels in the serum of patients with bladder cancer and suggested an association of elevated sFas level with poor prognosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some research shows that sFas can be detected in the urine or serum of the bladder cancer patients. We [ 4 , 5 ] and Svatek et al [ 6 ] noted that the urinary soluble Fas levels in patients undergoing surveillance for urothelial carcinoma were higher in cancer patients than the control group and that the urinary sFas was an independent predictor of bladder cancer recurrence and invasiveness in patients who had a past history of UC.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of survivin using ELISA reports a sensitivity of 71-85% with a specificity of 81-95% 12,13,60 . Soluble Fas was reported by two studies and showed varying sensitivity of 51% and 88% which suggesting a lack of reproducibility 16,61 .…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…Cystoscopy is unpleasant, time consuming, and expensive. Therefore, there has been an effort to replace it by a noninvasive diagnostic test, especially in patients with low-risk NMIBC [8,9,10]. However, noninvasive methods of bladder cancer detection still constitute a problem, especially when monitoring patients with a known diagnosis.…”
Section: Introductionmentioning
confidence: 99%